Graphene-supported dual-site catalysts for preparing self-reinforcing polyethylene reactor blends containing UHMWPE nanoplatelets and in situ UHMWPE shish-kebab nanofibers - Stürzel, Markus Roland; Thomann, Yi; Enders, Markus; Mülhaupt, Rolf (Macromolecules, 2014)
The catalytic ethylene polymerization on dual-site catalysts, supported on functionalized graphene, enables nanostructure formation in polyethylene reactor blends by in situ formation of uniformly dispersed ultrahigh molecular weight polyethylene (UHMWPE) nanoplatelets and in situ formed aligned UHMWPE shish-kebab nanofibers. For tailoring bimodal molar mass distributions, the quinolylsilylcyclopentadienylchromium(III) complex (Cr-1), producing UHMWPE with Mw > 3 × 106 g mol-1, is blended together with bisiminopyridine complexes of either chromium(III) (CrBIP), producing polyethylene (PE) wax (2 × 103 g mol-1), or iron(II) (FeBIP), producing PE with Mw = 2.0 × 105 g mol-1. Hence, the FeBIP/Cr-1 and CrBIP/Cr-1 molar ratios govern the PE/UHMWPE weight ratio without affecting the average molar mass of the individual PE fractions. In sharp contrast to conventional UHMWPE/PE reactor blends, the UHMWPE content is substantially increased up to 17 wt % without impairing melt processing. In the case of graphene-supported FeBIP/Cr-1, SEM and TEM analysis reveal that UHMWPE nanoplatelets are formed during polymerization. This is attributed to graphene-mediated mesoscopic shape replication. During injection molding, the UHMWPE nanoplatelets are transformed into aligned UHMWPE shish-kebab nanofibers, thus enabling efficient polyethylene matrix reinforcement.
Gesehen am 14.09.2020